PERAN PENDIDIK DALAM PENGELOLAAN MEDIA PEMBELAJARAN PADA SD/MI - Fatonah, Kuni (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
Teaching and learning is an activity that has educational value. The educational value colors the interactions that occur between teachers and students. Interaction that has value is directed at achieving certain goals that have been formulated before teaching is carried out. Teachers consciously plan their teaching activities systematically by utilizing everything, one of which is using technology media for creative, innovative and efficient teaching purposes, so it is hoped that students will not get bored and can get to know technology media that is developing rapidly in the current era. This research method uses library research that uses analysis from several sources, namely books, journals and other references to be drawn into conclusions as a result of the discussion. The results of this study indicate that the role of education in using learning media is very important and has an effect on students' capture of the lessons taught by the teacher, being able to understand what learning media are, criteria and stages of learning.